Literature and Disability - Hall, Alice (2015)
Literature and Disability introduces readers to the field of disability studies and the ways in which a focus on issues of impairment and the representation of disability can provide new approaches to reading and writing about literary texts. Disability plays a central role in much of the most celebrated literature, yet it is only in recent years that literary criticism has begun to consider the aesthetic, ethical and literary challenges that this poses.The author explores:key debates and issues in disability studies todaydifferent forms of impairment, with the aim of showing the diversity and ambiguity of the term "disability"the intersection between literary critical approaches to disability and feminist, post-colonial, and autobiographical writinggenre and representations of disability in relation to literary forms including novels, short stories, poems, plays and life writingThis volume provides students and academics with an accessible overview of literary critical approaches to disability representation.